Immunogenicity of PvCyRPA, PvCelTOS and Pvs25 chimeric recombinant protein of Plasmodium vivax in murine model - Matos, Ada da Silva; Soares, Isabela Ferreira; Rodrigues-da-Silva, Rodrigo Nunes; Rodolphi, Cinthia Magalhães; Albrecht, Letusa; Donassolo, Rafael Amaral; Lopez-Camacho, Cesar; Ano Bom, Ana Paula Dinis; Neves, Patrícia Cristina da Costa; Conte, Fernando de Paiva; Pratt-Riccio, Lilian Rose; Daniel-Ribeiro, Cláudio Tadeu; et al. (Frontiers in Immunology, 2024)
In the Americas, P. vivax is the predominant causative species of malaria, a debilitating and economically significant disease. Due to the complexity of the malaria parasite life cycle, a vaccine formulation with multiple antigens expressed in various parasite stages may represent an effective approach. Based on this, we previously designed and constructed a chimeric recombinant protein, PvRMC-1, composed by PvCyRPA, PvCelTOS, and Pvs25 epitopes. This chimeric protein was strongly recognized by naturally acquired antibodies from exposed population in the Brazilian Amazon. However, there was no investigation about the induced immune response of PvRMC-1. Therefore, in this work, we evaluated the immunogenicity of this chimeric antigen formulated in three distinct adjuvants: Stimune, AddaVax or Aluminum hydroxide (Al(OH)3) in BALB/c mice. Our results suggested that the chimeric protein PvRMC-1 were capable to generate humoral and cellular responses across all three formulations. Antibodies recognized full-length PvRMC-1 and linear B-cell epitopes from PvCyRPA, PvCelTOS, and Pvs25 individually. Moreover, mice's splenocytes were activated, producing IFN-γ in response to PvCelTOS and PvCyRPA peptide epitopes, affirming T-cell epitopes in the antigen. While aluminum hydroxide showed notable cellular response, Stimune and Addavax induced a more comprehensive immune response, encompassing both cellular and humoral components. Thus, our findings indicate that PvRMC-1 would be a promising multistage vaccine candidate that could advance to further preclinical studies.